2022
DOI: 10.3390/en15207542
|View full text |Cite
|
Sign up to set email alerts
|

Energy Use Forecasting with the Use of a Nested Structure Based on Fuzzy Cognitive Maps and Artificial Neural Networks

Abstract: The aim of this paper is to present a novel approach to energy use forecasting. We propose a nested fuzzy cognitive map in which each concept at a higher level can be decomposed into another fuzzy cognitive map, multilayer perceptron artificial neural network or long short-term memory network. Historical data related to energy consumption are used to construct a nested fuzzy cognitive map in order to better understand energy use behavior. Through the experiments, the usefulness of the nested structure in energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, the work of the application in a assisting PNS learning and development is still under covered, Through in-depth sentimental analysis, these inquiries promote a larger knowledge. Sentimental analysis is a technique that can provide a thorough understanding of people' sentiments and thoughts about a product or service [6,7]. Sentiment analysis will be utilized in this context to assess the quality of public service offered by the YuhSinau application.…”
Section: Icesrementioning
confidence: 99%
“…However, the work of the application in a assisting PNS learning and development is still under covered, Through in-depth sentimental analysis, these inquiries promote a larger knowledge. Sentimental analysis is a technique that can provide a thorough understanding of people' sentiments and thoughts about a product or service [6,7]. Sentiment analysis will be utilized in this context to assess the quality of public service offered by the YuhSinau application.…”
Section: Icesrementioning
confidence: 99%
“…From the literature review in [40], regarding power forecasting models in photovoltaic systems [64,65], it is concluded that the best results were obtained with the deep learning approach. Furthermore, it is concluded that most of the current deep learning algorithms are used to predict power loads of non-renewable energy sources [66][67][68][69], and that studies related to the prediction of renewable energy based on meteorological data are scarce; therefore, in this study, the WPNet model based on deep learning was developed. This model first has the data processing layer, another GRU layer, and finally the Dense layer.…”
Section: Simulationmentioning
confidence: 99%
“…Therefore, many other studies investigate the detection and diagnosis of failures of different components in photovoltaic systems [85][86][87][88][89], such as solar panel breakage (micro-cracks), broken solar cells or bypass diodes, wiring failures, potential induced degradation (PID) and short-circuit problems in power converters [88,89]. Work on the detection and classification of faults in PV installations using artificial intelligence techniques has been increasing [90][91][92], and not all studies include a system to alert the user when a failure occurs [69][70][71][72]. In [22], it was reported that DT technology was used for the operation and maintenance of solar energy systems, according to several studies, or the life cycle management of the solar plant [93], or for the monitoring of decentralised renewable energy sources [94].…”
Section: Fault Detection In Distributed Photovoltaic Systemsmentioning
confidence: 99%
“…They used the average temperature as an input variable to predict electrical loads for residential communities through the GRU model. Poczeta et al [22] combined fuzzy cognitive maps and artificial neural networks to construct an energy usage power load forecasting model. Pombo et al [23] integrated a PV performance model into a machine learning algorithm model to predict PV power using physical information features related to PV power generation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the existing deep learning algorithms are used for predicting power loads from non-renewable energy sources [17,18,20,22], while there is not enough research related to predicting renewable energy power based on weather data. Refs.…”
Section: Research Gap Contirbutions and Objectivesmentioning
confidence: 99%